Film, form, and culture - Kolker, Robert Phillip (Mc Graw-Hill, 2006)
The Film, Form, and Culture CD-ROM serves as a multimedia glossary or dictionary to ANY film text. It is available separately, and it can be packaged at a discount with any McGraw-Hill film title.